25-jarig jubileum J.W. Albarda als parlementariër. Plaats van personen aangegeven op achterzijde. Uit: Wij, 14 oktober 1938
25-jarig jubileum J.W. Albarda als parlementariër. Plaats van personen aangegeven op achterzijde. Uit: Wij, 14 oktober 1938.